2005
DOI: 10.1143/jjap.44.2691
|View full text |Cite
|
Sign up to set email alerts
|

Ge2Sb2Te5 Confined Structures and Integration of 64 Mb Phase-Change Random Access Memory

Abstract: Phase-change random access memory is considered a potential challenger for conventional memories, such as dynamic random access memory and flash memory due to its numerous advantages. Nevertheless, high reset current is the ultimate problem in developing high-density phase-change random access memory (PRAM). We focus on the adoption of Ge2Sb2Te5 confined structures to achieve lower reset currents. By changing from a normal to a GST confined structure, the reset current drops to as low as 0.8 mA. Eventually, ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 3 publications
0
22
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10] In both the optical and electrical phase-change data storage methods, data are written by locally melt quenching the crystalline phase-change film into an amorphous state using an optical ͑laser͒ or electrical pulse. The written amorphous bit can be read due to its large optical ͑reflectivity͒ or electrical ͑resistivity͒ contrast with the surrounding crystalline background.…”
Section: Influence Of Capping Layers On the Crystallization Of Doped mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] In both the optical and electrical phase-change data storage methods, data are written by locally melt quenching the crystalline phase-change film into an amorphous state using an optical ͑laser͒ or electrical pulse. The written amorphous bit can be read due to its large optical ͑reflectivity͒ or electrical ͑resistivity͒ contrast with the surrounding crystalline background.…”
Section: Influence Of Capping Layers On the Crystallization Of Doped mentioning
confidence: 99%
“…Since the endurance characteristic of PRAM has been reported to be approximately from 10 7 to 10 9 cycles [1,3,10], it is sufficient for the replacement of NOR flash memory, which is regarded as the first goal for commercial-level PRAM. However, to extend the application of PRAM to areas demanding powerful functions, additional improvement of device reliability is required in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…Due to repeated heating, a PCM cell can be reliably written only a limited number of times, which is referred to as write endurance. While an individual PCM cell can handle 10 12 write cycles [Lai and Lowrey 2001], experiments with PCM arrays and chips have shown much lower endurance in the range of 10 7 -10 9 writes [Burr et al 2010;ITRS 2009;Yeung et al 2005]. Write endurance is a significant obstacle that restricts PCM from serving as an immediate and widespread replacement for DRAM.…”
Section: Errors In Phase Change Memorymentioning
confidence: 99%
“…One major drawback is poor write endurance; a PCM cell can be reliably written only a restricted number of times. It has been reported that PCM chips can survive only 10 7 to 10 9 write cycles [Burr et al 2010;ITRS 2009;Yeung et al 2005]. This write endurance is significantly worse than DRAM, which promises at least 10 15 write cycles.…”
Section: Introductionmentioning
confidence: 99%